Effects of post-exercise heat exposure on acute recovery and training-induced performance adaptations: A systematic review - Ahokas, E. K.; Hennessy, R. S.; Hanstock, H. G.; Kyröläinen, H.; Ihalainen, J. K. (Sports Medicine - Open, 2025)
Background Whole-body heat exposure, such as sauna bathing or hot water immersion (HWI) has been shown to induce various physiological adaptations that can improve athletic performance. However, the effects of post-exercise heat exposure on acute recovery and promoting training-induced performance adaptations are not well understood. The aim of this systematic review was to summarise the current evidence on the effects of post-exercise heat exposure on physical performance in healthy adults.